Prevalence of malocclusion in Turkish children and adolescents: A systematic review and meta‐analysis - Jimmy Londono; Shohreh Ghasemi; Negar Moghaddasi; Homa Baninajarian; Amir Fahimipour; Sara Hashemi; Amirhossein Fathi; Mahmood Dashti (Wiley, 2023)
Abstract Objectives The aim of this article is to establish a comprehensive nationwide prevalence of malocclusion traits on the sagittal, vertical, and transverse planes of space in the Turkish population. Material and Methods A systematic search of PubMed, Scopus, and Web of Science was supplemented by manual searches of Google Scholar and the reference lists of included studies. Original Turkish health studies of any age were included. Strengthening the Reporting of Observational Studies in Epidemiology assessed study quality and bias (STROBE). Sagittal, vertical, and transverse malocclusion features were retrieved and gathered. Results Eleven studies were selected from 434 titles. Two studies showed a high risk of bias, eight low and one moderate. Thirteen thousand two hundred seventy‐one individuals were investigated from early childhood to late adulthood. Most studies were sampled from universities and dental (nonorthodontic) clinics. The pooled malocclusion prevalence was 56% for Class I (95% confidence interval (CI): 44−68%), 31% for Class II (CI: 6-42%), and 11% for Class III (CI: 21-37%). The other common types of malocclusions were crowding (41%, CI: 18-65%), overjet (34%, CI: 21-50%), negative overjet (13%, CI: 7-20%), and crossbite (11%, CI: 7-15%). Additionally, there was no significant difference in Class I (relative risk [RR] = 1.00, [0.96-1.05]), Class II ([RR] = 0.97, [0.92-1.03]), and Class III ([RR] = 1.08, [0.96-1.225]) malocclusion by gender. Conclusions This study showed Class I malocclusion has a high prevalence among the Turkish population followed by Class II and Class III malocclusions. In addition, crowding and overjet were the most prevalent malocclusions among Turkish individuals. There were no significant differences in the prevalence of malocclusions between males and females.